PENGARUH VARIASI DIAMETER PULLEY PADA MESIN PERAJANG BAWANG MERAH TERHADAP KAPASITAS RAJANGAN - Cryzna Rizky Hermawan; Sri Widodo; Catur Pramono; Sri Hastuti (Journal of Mechanical Engineering, 2018)
This study of the influence of variations in pulley diameter driven on shallot chopper machines against the chaff yield capacity is motivated by the production and consumption of shallots in Indonesia is quite high, so it takes a red onion chopper machine to facilitate the handling and processing. The purpose of this study was to make a shallot chopper machine, to analyze the effect of variations in pulley diameter on the yield of onion chopping, and to analyze the results of onion chopping. In this study, the analyzed were chopper speed with variations in pulley diameter driven 6 inch, 7 inch, 8 inch and 1½ inch drive pulley diameter. The test method uses 200 grams of shallots per experiment with repetitions three times the experiment with variations of pulley driven 6 inches, 7 inches, and 8 inches. After testing, an analysis of the data obtained in the form of chaff yield capacity is completed. The best test results were obtained using variations in pulley diameter driven by 6 inches with a chopping yield capacity of 3.77 grams / second.